Aqueous Cytokines in Sympathetic Ophthalmia Following Complications of Intravitreal Aflibercept. (September 2019) - Juncal, Verena R.; Cho, Ryan; Bakshi, Nupura; Ghaffar, Hasan; Yucel, Yeni Y.; Muni, Rajeev H.
Purpose: This article reports a case of sympathetic ophthalmia (SO) following complications from bilateral intravitreal aflibercept injections, including infectious endophthalmitis requiring vitreoretinal surgery in the left eye (OS) and sterile intraocular inflammation in the right eye (OD), and describes the aqueous cytokine profile of this patient. Methods: The patient was a 51-year-old man with SO. Cytokine levels in the aqueous humor of the sympathizing eye were measured at presentation. Results: A patient being treated with bilateral aflibercept injections for diabetic macular edema developed infectious endophthalmitis OS requiring a pars plana vitrectomy and sterile intraocular inflammation OD, which subsequently led to SO. Enucleation of the exciting eye (OS) was performed and histopathology confirmed the diagnosis. Cytokine levels in the sympathizing eye revealed high concentrations of intercellular adhesion molecule-1, inducible protein-10, and interleukin-8 and -10. Conclusions: SO can occur after vitreoretinal surgery for endophthalmitis in the exciting eye and sterile intraocular inflammation in the sympathizing eye following aflibercept injections.